Minnesota multiphasic personality inventory of school sandplay group therapy with maladjustment behavior in Korean adolescent - Ahn, Un Kyoung (Medicine (Baltimore), 2020)
School sandplay group therapy is a useful clinical treatment method for adolescents who cannot adapt to school due to various emotional and behavioral problems. In this study, we conducted 10 weeks of group therapy in 70 adolescents referred to as maladjustment behavior problem in the school. The purpose of this study was to evaluate the clinical effects of sandplay therapy on the emotions and behaviors objectively through minnesota multiphasic personality test -2. There was a statistically significant difference in clinical scales such as depression, masculinity- femininity, social introversion, anger, subjective depression, need for affection, somatic complaint, and internal/external alienation after school sandplay group therapy. Sandplay therapy is estimated to have clinical effects not only on the emotional problems of maladapted high school students but also on physical problems.